LABELLED BRACKET IN CONSTRUCTING NOUN PHRASE OF COLLEGE STUDENTS’ NARRATIVE COMPOSITIONS - Sulistiani Anita; Winatu Kurnianingtyas Sri Agung (ELITE JOURNAL, 2019)
The main core in sentence is noun phrase because of its important functions as subject, object, and complement. In constructing noun phrase based on the functions, it has characteristics of components structure. Thus, its functions and the components have to be understood by second language learners well to create and compose a good sentence. This article investigates the constructions of English College Students’ Compositions at IAIN Ponorogo. In analyzing that problem, qualitative research was conducted and the documentation of narrative texts of 24 TIA students were collected and syntactical analysis with labelled bracket was applied to analyze the construction of noun phrase. The findings revealed that there were 479 sentences in students’ writing compositions and four types of noun phrase constructions found in those sentences. They were 469 sentences constructed from pre-modifier and head, 453 sentences were head itself, 25 sentences were constructed from head and post-modifier and pre-modifier, head and post-modifier were defined in 113 sentences. Noun phrase has different forms and functions in sentences which the college students have to understand well. Indeed, the students are able to identify the parts of noun phase easily through labeled bracket.